2016
DOI: 10.1177/1741143215578448
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ perceptions of school leaders’ empowering behaviours and psychological empowerment

Abstract: Using a convenience sample of 289 teachers in Singapore, this study examined: (1) whether there were significant differences between teachers’ perceptions of principal’s and immediate supervisor’s empowering behaviours; and (2) teachers’ perceptions of principal’s and immediate supervisor’s empowering behaviours in relation to teachers’ psychological empowerment. Results indicated that teachers perceived their principals and immediate supervisors as exercising empowering behaviours in their daily practices, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 75 publications
0
26
1
5
Order By: Relevance
“…Fourth, teachers perceived higher autonomy to innovate after a series of teacher training activities. Previous studies emphasized the importance of collaborative leadership style in policy making, delegation of autonomy, open vision and willingness to take risks for introducing ICT into educational activities [49][50][51]. Interviews with local school leaders who facilitated the teacher training activities confirmed that school leaders themselves were aware of the advantage and thus encouraged teachers to be innovative in its use.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Fourth, teachers perceived higher autonomy to innovate after a series of teacher training activities. Previous studies emphasized the importance of collaborative leadership style in policy making, delegation of autonomy, open vision and willingness to take risks for introducing ICT into educational activities [49][50][51]. Interviews with local school leaders who facilitated the teacher training activities confirmed that school leaders themselves were aware of the advantage and thus encouraged teachers to be innovative in its use.…”
Section: Discussionmentioning
confidence: 97%
“…Teachers felt that being able to reach out to others reduces the anxieties about exposing a lack of certain skills. Lee and Nie [51] studied the teachers' perception on school leadership and found that behaviors such as delegating authority and providing individualized concern and support could empower teachers to be more active in school activities.…”
Section: School Leadership Supportmentioning
confidence: 99%
“…As reform champions and change agents, teacher-leaders play a multiplicity of roles as mentors (Clarke, Killeavy, & Ferris, 2015), servant leaders (Nichols, 2011), team players (Koeslag-Kreunen, Van der Klink, Van den Bossche, & Gijselaers, 2018), team leaders (Honingh & van Genugten, 2017), curriculum reformers (Zhang & Henderson, 2018), and student character builders (Ningsih & Wijayanti, 2018). Teacher leaders perform these duties to varying degrees of involvement while relying mainly on their psychological resources (Lee & Nie, 2017;Lyness, Lurie, Ward, Mooney, & Lambert, 2013). Political skill is one psychological resource teacher-leaders seldom neglect to employ in doing what they do.…”
Section: Teacher-leader Political Skillmentioning
confidence: 99%
“…Το σχολικό περιβάλλον αλλά και η ευρύτερη τοπική κοινότητα επηρεάζουν τα συναισθήματα του εκπαιδευτικού, ακόμη και τις ίδιες τις πεποιθήσεις και στάσεις του (Rubie-Davies, Flint & McDonald, 2012), οι οποίες με τη σειρά τους θα καθορίσουν τις διδακτικές του επιλογές (O'Brennan, Bradshaw & Furlong, 2014). Γενικότερα το κοινωνικό περιβάλλον επιδρά στην ταυτότητα του εκπαιδευτικού (Lasky, 2005), ενώ η διαμόρφωση του ρόλου του και οι διδακτικές του επιλογές δεν πηγάζουν αποκλειστικά από το αξιακό του σύστημα, αλλά συν-διαμορφώνονται από τις αξίες που προάγονται στο εργασιακό και κοινωνικό περιβάλλον στο οποίο εντάσσεται (Lee & Nie, 2017).…”
Section: βιβλιογραφική επισκόπησηunclassified